Minimum Wage in Poland and Youth Employment in Regional Labor Markets. Issue 9 (1st September 2016) - Majchrowska, Aleksandra; Broniatowska, Paulina; Żółkiewski, Zbigniew
ABSTRACT: The aim of this article is to analyze the effect of a uniform minimum wage in Poland on youth employment in regional labor markets and to determine in which of the regions the effect is significant. The analyses are based on NUTS2 level in 1999–2012. The results point to a statistically insignificant parameter of minimum wage variable for the whole sample. However, after allowing the minimum wage parameter to vary across regions, we find that the relatively high ratio of minimum to average wages could be the factor limiting youth employment growth in less-developed regions in the southeast of Poland.